Auxin-induced Changes in Avena Coleoptile Cell Wall Composition - Loescher, Wayne (1972)
Sugar and uronic acid residues were derived from wall polysaccharides of oat (Avena sativa, var. Victory) coleoptiles by means of 2 N trifluoroacetic acid, 72% sulfuric acid, or enzymic hydrolysis. The products of hydrolysis were reduced and acetylated to form alditol acetates which were analyzed using gas chromatography. Time-course studies of auxin-promoted changes in various wall fractions indicate that when exogenous glucose was available, increases in certain wall constituents paralleled increases in length. However, under conditions where exogenous glucose was not available, and where wall synthesis was limited, such correlations with growth were not apparent. Under these latter conditions total wall weight initially increased slightly, then decreased. These changes in weight were the net of increases in cellulose and some noncellulosic constituents and a decrease of over 75% in noncellulosic glucose. When coleoptile sections were preincubated without exogenous glucose for 8 hours to deplete endogenous wall precursors and subsequently treated with auxin, there were no detectable increases in wall weight. There was instead an auxin-promoted decrease in wall weight, and this decrease paralleled a decrease in noncellulosic glucose. There were no significant changes in other wall components. The auxin-promoted decreases in noncellulosic glucose are interpreted as a possible step in the mechanism of growth.